Epidemiological and Clinical profile of HIV-infected patients attending HIV clinic at Sekou Toure Referral and Teaching Hospital in Mwanza, Tanzania: 4 years review (Tanzania Medical Journal, 2017)
Background: Treatment and care services for HIV patients in Tanzania began 2004 with free access to anti-retroviral therapy (ART). More than 1000 HIV clinics have been established to-date. Each clinic is obliged to provide statistical and clinical feedback for further improvement.Broad objective: The objective of this study was to establish baseline epidemiological and clinical characteristics of patients who are ART naïve attending Sekou Toure Regional and Referral HIV clinic.Methodology: We retrospectively analyzed data for four years between 2004 and 2008 from the Sekou Toure HIV clinic database. We included all patients aged 18 and above who were eligible to commence ART. All pregnant women and patients being transferred in or out of the centre were excluded from this study. The statistical data analysis was performed using STATA program, version 14 (College Station, Texas).Results: We analyzed 726 patients, and among them 487 (67.2%) were females. The median age was 38 (IQR= 33-44) years.. The majority of these patients (58%) were in advanced clinical HIV stages (III and IV) with low baseline CD4 cell count (118cells/µl [IQR 46-200]. Tuberculosis was the leading opportunistic infection (OI) in over 80% of patients who had at least one OI at enrolment.Conclusion and recommendation: This study is important, as it has established the baseline data for further research and follow-up of these patients especially with the current improvement of Care and Treatment services in the country as compared to the previous time.